KEWARISAN ANAK HASIL PROSES BAYI TABUNG (Wasiat Wajibah Sebagai Hak Waris Anak Hasil Surrogate Mother Ditinjau Dari Berbagai Aspek Hukum Di Indonesia) - Nur Komala (Indonesian Journal of Islamic Law, 2018)
The inheritance status of children born through in vitro fertilization involving a surrogate mother carries significant implications for the legal position of the child in civil law, particularly concerning legal certainty regarding inheritance rights. This study employs a normative legal method and is conducted as library research by examining existing legal regulations in Indonesia, including the Civil Code, Child Protection Law, Criminal Law, Human Rights Law, Health Law, as well as legal perspectives from technology, economics, and Islamic law. The conclusion of this study is that children born through surrogate mothers fall into two categories: first, they are classified as children born out of wedlock, as they are born outside a legally recognized marriage; second, they may be classified as adopted children if the married couple chooses to adopt them, in which case their status is that of adopted children rather than biological children. Both children born out of wedlock and adopted children are entitled to inheritance in the form of a mandatory bequest (wasiat wajibah) amounting to one-third of the estate, as determined by the Religious Court with final and binding legal force. Such children only have civil legal relations with their biological mother and her family.